Lead removal and recovery by crystallization process in a fluidized-bed reactor - Asiao, Riño N.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2014)
Lead (Pb) is one of the heavy metals having a high and long-term toxicity even very low concentration which limits the reusability and recyclability of industrial wastewaters. In this study, the removal and recovery of Pb from synthetic wastewater by crystallization process in a fluidized-bed reactor was investigated. Pb removal efficiencies exceed 99% when the operating pH was kept within 8-9 range and [CO3 2- : Pb2+ ] molar rati was 3:1. Higher [CO3 2- : Pb2+ ] molar rati was 3:1. Higher Pb removal efficiencies were obtained with the gradual reduction of recirculation rate. The particle size distribution of collected crystals showed that aggregation and crystal growth were influenced by the duration of fluidization. X-ray diffraction XRD)analysis proved that the collected crystals were orthorhombic PbCO3 crystals similar to that of cerrusite.Energy-dispersive X-ray spectroscopy (EDS)data showed that Pb,C and O elements in thee collected crystals were in proportionate amounts to form PBCO3.elements in thee collected crystals were in proportionate amounts to form PBCO3. The present study demonstrates that Pb can be successfully removed and recovered as PbCO3 crystals in a fluidized-bed reactor.
Thesis (M.S. in Environmental Engineering)--University of the Philippines Diliman
Keywords: Water -- Purification -- Lead removal; Fluidization; Fluidized reactors